The ROLE OF IMMIGRATION OFFICE CLASS II TPI LHOKSEUMAWE: DYNAMICS OF HANDLING ROHINGYA REFUGEES IN 2015-2022: PERAN KANTOR IMIGRASI KELAS II TPI LHOKSEUMAWE : DINAMIKA PENANGANAN PENGUNGSI ROHINGYA TAHUN 2015-2022 - Hidayatullah, Syarif; Novialdi, Risky (Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pasundan, 2023)
Abstract This thesis will focus on the role of the Immigration Office Class II TPI Lhokseumawe and the dynamics that occur in the handling of Rohingya refugees stranded in Aceh province from 2015 to 2022. Aceh province is always visited by Rohingya refugees every year, the Immigration Office Class II TPI Lhokseumawe which has a scope of work in three city districts has repeatedly participated in handling Rohingya refugees. It should be noted that Indonesia is not a country that participated in ratifying the 1951 Convention related to international refugees, but nevertheless Indonesia showed its action in this case. The writing of this thesis uses descriptive qualitative research techniques. The information data in this thesis is sourced from secondary data library research and premier data interviews related workers. The use of inductive analysis techniques is done to find the suitability of facts with the theory used in writing this thesis. The conclusion in this thesis will explain the dynamics that occur in the handling of Rohingya refugees from 2015 to 2022 and the role of the Lhokseumawe Class II TPI Immigration Office in handling Rohingya refugees. Keywords: Rohingya, Role, Immigration, Aceh, Refugees, R2p, Dynamics. Abstrak Tulisan dari skripsi ini berfokus pada peran kantor Imigrasi kelas II TPI Lhokseumawe dan dinamika yang terjadi dalam penanganan pengungsi Rohingya yang terdampar di provinsi Aceh dengan rentang tahun 2015 hingga 2022. Provinsi Aceh setiap tahunya selalu didatangi pengungsi Rohingya, Kantor Imigrasi Kelas II TPI Lhokseumawe yang memiliki ruang lingkup kerja di tiga kabupaten kota telah berulang kali ikut terlibat dalam penanganan pengungsi Rohingya. Penulisan skripsi ini menggunakan teknik penelitian deskriptif kualitatif. Data informasi pada skripsi ini bersumber dari data sekunder library research dan data premier wawancara pekerja terkait. Penggunaan teknik analisa induktif, dilakukan untuk menemukan kesesuaian fakta dengan teori yang digunakan dalam penulisan skripsi ini. Adapun hasil penelitian ini menjelaskan dinamika yang terjadi dalam penanganan pengungsi Rohingya tahun 2015 hingga 2022 dan peran dari Kantor Imigrasi Kelas II TPI Lhokseumawe dalam penanganan pengungsi Rohingya. Kata-kata Kunci: Rohingya, Peran, Imigrasi, Aceh, Pengungsi, R2p, Dinamika.